A review on the research progress on non-pharmacological therapy of Helicobacter pylori - Luo, Qian; Liu, Na; Pu, Sugui; Zhuang, Ze; Gong, Hang; Zhang, Dekui (Frontiers in Microbiology, 2023)
Helicobacter pylori is a pathogenic microorganism that mainly resides in the human stomach and is the major cause of chronic gastritis, peptic ulcer and gastric cancer. Up to now, the treatment of Helicobacter pylori has been predominantly based on a combination of antibiotics and proton pump inhibitors. However, the increasing antibiotic resistance greatly limits the efficacy of anti-Helicobacter pylori treatment. Turning to non-antibiotic or non-pharmacological treatment is expected to solve this problem and may become a new strategy for treating Helicobacter pylori. In this review, we outline Helicobacter pylori's colonization and virulence mechanisms. Moreover, a series of non-pharmacological treatment methods for Helicobacter pylori and their mechanisms are carefully summarized, including probiotics, oxygen-rich environment or hyperbaric oxygen therapy, antibacterial photodynamic therapy, nanomaterials, antimicrobial peptide therapy, phage therapy and modified lysins. Finally, we provide a comprehensive overview of the challenges and perspectives in developing new medical technologies for treating Helicobacter pylori without drugs.